Analysis of Trend of Studies on Microneedle Treatment System (MTS) - Hea-Sun Chun; Ho-Seub Song (Korean Pharmacopuncture Institute, 2021)
bjectives: The purpose of this study was to analyze the microneedle therapy system (MTS) and its research methods for the past 10 years in Korea.Methods : Data on microneedle therapy system were collected using NDSL, KISS, RISS, and OASIS electronic databases from January 2010 to August 2021. "microneedle," "derma stamp," "microneedle therapy system" were used as the keywords. The present study, however, excluded data that were 1) unrelated to the microneedle therapy system, 2) from review/meta/protocol studies, and 3) from overseas studies. Data selected through the primary screening process, animal studies, case reports, and clinical data were included in the analysis. However, information data not related to the microneedle therapy system were excluded from the study.Results : Among the MTS-related papers published from January 2010 to August 2021, 7 animal research, 2 clinical trials, and 10 case studies were published. Based on the research topics, there were 8 papers on skin improvement and skin diseases, 7 papers on hair growth and hair loss, 3 papers on stability, and 1 paper on peripheral facial paralysis.Conclusion : Most of the studies related to MTS focused on skin, hair, and stability. The effect of MTS on hair growth and skin improvement has been confirmed, and it has been proven to have significant effects on the treatment of acne, acne scars, and hair loss in clinical practice. No serious side effects were observed during the MTS treatment, and the safety assessment confirmed that it was safe for use.